2021
DOI: 10.35633/inmateh-64-10
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characteristics of the Rubbed Maize Straw During Screw Conveying

Abstract: In order to reduce the power consumption of screw conveyor and to improve the productivity, this study investigated such mechanical characteristics of rubbed maize straw as coefficient of sliding friction, angle of repose, internal friction coefficient, cohesion, flow function value and compressible coefficient with respect to its moisture content and density. An experiment was designed and consists of a sliding friction characteristic test-bed, a direct shear apparatus, a self-made device with adjustable dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The above two teams the response surface method mainly for the selection of important influencing parameters. Meanwhile, the response surface method can used for more detailed optimization of parameters, such as Chunguang Wang's team in the study of kneading corn straw screw conveying device to optimize the screw pitch, screw shaft speed, and feeding volume of three parameters, and finally obtain the optimal combination of parameters, so that the overall performance of the device can be improved [41]. In the same way, Wanzhang Wang's team also used the response surface method to optimize the vibration parameters in the lifting device of the tiger fruit harvester to obtain the optimal parameters of vibration frequency, vibration amplitude, lifting speed and lifting angle, and the results of the study provide theoretical references for the design optimization and simulation analysis of the tiger fruit harvester [42].…”
Section: Discussionmentioning
confidence: 99%
“…The above two teams the response surface method mainly for the selection of important influencing parameters. Meanwhile, the response surface method can used for more detailed optimization of parameters, such as Chunguang Wang's team in the study of kneading corn straw screw conveying device to optimize the screw pitch, screw shaft speed, and feeding volume of three parameters, and finally obtain the optimal combination of parameters, so that the overall performance of the device can be improved [41]. In the same way, Wanzhang Wang's team also used the response surface method to optimize the vibration parameters in the lifting device of the tiger fruit harvester to obtain the optimal parameters of vibration frequency, vibration amplitude, lifting speed and lifting angle, and the results of the study provide theoretical references for the design optimization and simulation analysis of the tiger fruit harvester [42].…”
Section: Discussionmentioning
confidence: 99%
“…The gap partitioning hypothesis suggests that resource heterogeneity allows ecological niche redistribution for stable forests [188], with regenerating tree species regenerating and spreading along the gap environment gradient according to varying resource demands [189]. In some relatively barren habitats, where the plasticity intensity and light range width of the tree species are most important [190], individual trees have genetically determined growth strategies; fast-growing genotypes are more common in light-rich environments [191], and vegetation in forest gaps has a greater competitive advantage with higher light and water availability [192]. However, community assemblages are controlled by local ecology (limited ecological niches).…”
Section: Effects Of Forest Gap Disturbance On Regenerationmentioning
confidence: 99%
“…Among them, the screw conveyor is widely used in the processing of cornstalk because it is compact and airtight, its assembly is flexible, and its feed is adjustable. However, its transportation performance is unstable due to the characteristics of cornstalk, such as light density, high viscosity and poor fluidity (Wulantuya et al, 2019a). To date, the study of screw conveyors for fibrous agricultural materials has mainly focused on equipment for harvesting and processing (Kaplan et al, 2012;Jiang et al, 2013;Feng et al, 2015;Nachenius et al, 2015a andNachenius et al, 2015b;Chamberlin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the study of screw conveyors for fibrous agricultural materials has mainly focused on equipment for harvesting and processing (Kaplan et al, 2012;Jiang et al, 2013;Feng et al, 2015;Nachenius et al, 2015a andNachenius et al, 2015b;Chamberlin et al, 2018). Our team previously investigated the screw conveying process of chopped cornstalk and found that the biomass material underwent overall screw-type motion under the joint effects of below-normal thrust and tangential friction of the screw blades and axial and circumferential friction of the screw shaft and interior casing (Wulantuya et al, 2015(Wulantuya et al, , 2016(Wulantuya et al, and 2019a. The chopped cornstalk was constantly squeezed Engenharia Agrícola, Jaboticabal, v.43, n.3, e20220068, 2023 during transportation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation